Injectable nano-structured silicon-containing hydroxyapatite microspheres with enhanced osteogenic differentiation and angiogenic factor expression. Issue 16 (November 2018) - Sun, Wenjun; Zhou, Yuning; Zhang, Xinran; Xia, Wei; Xu, Yuanjin; Lin, Kaili
Abstract: Injectable bioactive ceramics with excellent osteogenesis play important roles in bone regeneration field. In this study, we creatively fabricated the injectable nano-structured silicon-containing hydroxyapatite (Si-HAp) microspheres in diameter of 70–100 µm via hydrothermal treatment of calcium silicate (CaSiO3 ) microspheres in Na3 PO4 aqueous solution. The fabricated Si-HAp microspheres were constructed by nano-rods with a diameter of 100 nm and length up to 1.5 µm. Comparing with the pure HAp microspheres, the obtained nano-structured Si-HAp microspheres exhibited excellent protein loading properties and sustained protein release capacities. Most importantly, the Si-substitution could apparently enhance the proliferation, osteogenic differentiation and the genes expression of angiogenic factors of rat bone marrow mesenchymal stem cells (rBMSCs). These all indicated that the nano-structured Si-HAp microspheres fabricated via hydrothermal transformation method might be used as promising injectable bioactive biomaterials and drug deliveries for bone regeneration.